Host range evaluation and morphological characterization of Pseudoperonospora cubensis, the causal agent of cucurbit downy mildew in Malaysia - Salati, Mansour; Wong, Mui Yun; Meon, Sariah; Nik Hassan, Nik Masdek (Academic Journals, 2010)
A total of 29 isolates of Pseudoperonospora cubensis were collected from various cucurbit farms in West Malaysia. Sporangia of 13 isolates had the ability to germinate at 14°C and were used for host range (pathotype) study using leaf disc assay on a set of twelve cucurbit cultivars. Twelve different pathotypes of P. cubensis were determined and this demonstrated that P. cubensis isolates from cucurbit farms in West Malaysia are highly variable. Based on the host range study, majority of P. cubensis isolates were categorized into medium and high pathogenicity groupings and this fact shows the potential of this pathogen in invading cucurbit fields in the tropical regions. However, the pathotypes could not be differentiated based on morphological characterization of the sporangia and sporangiophores. Therefore, molecular characterization of the 13 isolates of P. cubensis will be useful to study the relationships among them.